Immunological and clinical impact of manipulated and unmanipulated DLI after allogeneic stem cell transplantation of AML patients - Greiner, Jochen; Hofmann, Susanne (Journal of Clinical Medicine, 2020)
Allogeneic stem cell transplantation (allo-SCT) is the preferred curative treatment for several hematological malignancies. The efficacy of allo-SCT depends on the graft-versus-leukemia (GvL) effect. However, the prognosis of patients with relapsed acute myeloid leukemia (AML) following allo-SCT is poor. Donor lymphocyte infusion (DLI) is utilized after allo-SCT in this setting to prevent relapse, to prolong progression free survival, to establish full donor chimerism and to restore the GvL effect in patients with hematological malignancies. Thus, there are different options for the administration of DLI in AML patients. DLI is currently used prophylactically and in the setting of an overt relapse. In addition, in the minimal residual disease (MRD) setting, DLI may be a possibility to improve overall survival. However, DLI might increase the risk of severe life-threatening complications such as graft-versus-host disease (GvHD) as well as severe infections. The transfusion of lymphocytes has been tested not only for the treatment of hematological malignancies but also chronic infections. In this context, manipulated DLI in a prophylactic or therapeutic approach are an option, e.g., virus-specific DLI using different selection methods or antigen-specific DLI such as peptide-specific CD8+ cytotoxic T lymphocytes (CTLs). In addition, T cells are also genetically engineered, using both chimeric antigen receptor (CAR) genetically modified T cells and T cell receptor (TCR) genetically modified T cells. T cell therapies in general have the potential to enhance antitumor immunity, augment vaccine efficacy, and limit graft-versus-host disease after allo-SCT. The focus of this review is to discuss the different strategies to use donor lymphocytes after allo-SCT. Our objective is to give an insight into the functional effects of DLI on immunogenic antigen recognition for a better understanding of the mechanisms of DLI. To ultimately increase the GvL potency without raising the risk of GvHD at the same time.